1981
DOI: 10.1177/002246698101500110
|View full text |Cite
|
Sign up to set email alerts
|

School Psychology and Special Education Students' Placement Decisions: IQ Still Tips the Scale

Abstract: Syracuse University's Psychoeducational Teaching Laboratory attempted to evaluate how well it was transmitting the principles of multidimensional and nonbiased assessment practices to its students. School psychology and special education graduate students were asked to make program placement decisions for a child when given data about IQ, adaptive behavior higher than IQ, and academic achievement. Results indicated that the school psychology and special education programs were equally successful in training st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Similar results were obtained in my other studies. These findings are also consistent with the reports of other researchers using analogue methodology, which showed that test data, particularly achievement data (Hannaford et al, 1975; Kavale & Andreassen, 1984), influenced SE decisions (Burns, 1990a; Hannaford et al 1975; Knoff, 1984; Matuszek & Oakland, 1979; Smith & Knoff, 1981). Naturalistic studies, which have investigated differences between students who were referred and placed in SE vs. students who were referred and not placed in SE, have further documented the importance of test data (Huebner & Cummings, 1986b; Olson & Midgett, 1984; Sexton & Street, 1985; Sinclair & Alexson, 1986; Wilson, Cone, Bradley & Reese, 1986).…”
Section: Assessment Informationsupporting
confidence: 91%
“…Similar results were obtained in my other studies. These findings are also consistent with the reports of other researchers using analogue methodology, which showed that test data, particularly achievement data (Hannaford et al, 1975; Kavale & Andreassen, 1984), influenced SE decisions (Burns, 1990a; Hannaford et al 1975; Knoff, 1984; Matuszek & Oakland, 1979; Smith & Knoff, 1981). Naturalistic studies, which have investigated differences between students who were referred and placed in SE vs. students who were referred and not placed in SE, have further documented the importance of test data (Huebner & Cummings, 1986b; Olson & Midgett, 1984; Sexton & Street, 1985; Sinclair & Alexson, 1986; Wilson, Cone, Bradley & Reese, 1986).…”
Section: Assessment Informationsupporting
confidence: 91%
“…It is relatively easy to enter but difficult to return to the regular class (Galvin & Elliott, 1985). It should be noted that our findings fit within a body of simulation literature that suggests that school psychologists make databased decisions (Johnson, 1980; Knoff, 1983; Matuszek & Oakland, 1979; Pfeiffer & Naglieri, 1984; Smith & Knoff, 1981). In general, these studies have focused on classification decisions for children with suspected mental retardation.…”
Section: Discussionsupporting
confidence: 78%
“…We anticipated negative relations between likelihood to refer and teachers' parenthood (Harasymiw & Home, 1976;Smith &: Knoff, 1981), experience in mixed grade classrooms, and special education experience (DeStefano, Gesten, & Cowen, 1977;Harasymiw 8c Home, 1976). Regarding class size, we expected that teachers of larger classes would be more likely to refer than those in smaller classes (see Gerber & Semmel, 1984).…”
mentioning
confidence: 99%